Transformation of Human Capital Management in Telecommunications Enterprises under the Influence of Digitalization - Zavgorodnii, A. O.; Soroka, A. M.; Petchenko, M. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article explores the theoretical and methodological foundations and practical aspects of human capital management transformation in telecommunication enterprises under the influence of global digitalization. Key drivers of these changes, including customer needs, competitive challenges, and systemic innovations, are outlined. The directions of digital transformation of HR processes, encompassing the implementation of artificial intelligence, Big Data analytics, gamification, and automation of routine tasks, are analyzed. Special attention is paid to the influence of digitalization on the formation of the innovative-intellectual flow as a dominant component of the enterprises’ integrative development. An analytical toolkit for evaluating digital transformation processes in the personnel management system is proposed. The necessity of transitioning to proactive adaptive management, based on new digital competencies of personnel and ensuring sustainable competitive advantages for telecommunication companies, is substantiated.